PENGARUH KUALITAS PRODUK, KUALITAS LAYANAN, CITRA MEREK, DAN PERSEPSI HARGA TERHADAP MINAT BELI ULANG MOBIL MEREK TOYOTA DI PT. NASMOCO SEMARANG ( Studi pada Konsmen Pengguna Mobil Merek Toyota di Semarang ) - Dwi Kurniawan Novianto, 14.05.51.0251; Basiya, Robertus (Students' Journal of Economic and Management, 2018)
This study aims to examine the effect of Product Quality, Service Quality, Brand Image, and Price Perception on Buying Interest. The population in this study is Consumer Users of Toyota Brand Car in Semarang. Samples were taken as many as 100 respondents by using purposive accidential sampling technique. Data were collected using survey method through questionnaires filled by consumers.Analytical technique using multiple regression method previously tested the validity and reliability test. In addition, this study also used F statistical tests and coefficient of determination. The latter performed hypothesis testing using t test.The result of this research shows that product quality variable have positive and significant effect to Repurchase Intention, Quality of Service have positive but not significant effect to Repurchase Intention, Brand Image have positive and significant effect to Repurchase Intention and Reflect Price Interest have positive and significant influence to Repurchase Intention. Keywords: Product Quality, Service Quality, Brand Image, Price Perception, and Repurchase Intention.